Roman warships - Pitassi, Michael (The Boydell Press, 2011)
Part II. INTERPRETATION. 1. Sources -- 2. Interpreting the Sources -- 3. Ship Fittings -- PART II THE SHIPS. 4. The Earliest Types: Eighth to Fourth Centuries BC -- 5. Naval Ascendancy: Third and Second Centuries BC -- 6. Civil Wars and Imperial Fleets: First Centuries BC and AD -- 7. Height of Empire: Second and Third Centuries AD -- 8. The Late Empire: Fourth and Fifth Centuries AD -- 9. Terminus.